Electron heating and acceleration while magnetosphere substorm due to varying whistler wave phase velocity - Karas, V.I.; Potapenko, I.F. (Вопросы атомной науки и техники, 2007)
Some properties of chorus radiation while magnetosphere substorm are discussed. The influence of the hydro magnetic waves on the electron distribution function is studied by numerical simulations. A quasi-linear 2D in velocity space operator models the electron damping of plasma eigenmodes. The dynamic of process is estimated under condition of varying in time of phase velocity and hence of phase resonance on the base of chorus radiation while substorms. This allows us to explain acceleration and heating of energetic electrons that double up energy during the stage of substorm. Обговорюються деякі властивості хорового випромінювання. Чисельними методами досліджується вплив магнітогідродинамічних хвиль на функцію розподілу електронів. Квазілінійний двовимірний у просторі швидкостей оператор моделює електронне затухання плазмових власних хвиль. Динаміка процесу описана в умовах, коли змінюється за часом фазова швидкість, а, тому, і фазовий резонанс, на основі хорового випромінювання під час суббурі. Це дозволило нам пояснити прискорення і нагрів енергетичних електронів, котрі подвоюють свою енергію під час стадії суббурі. Обсуждаются некоторые свойства хорового излучения. Численными методами исследуется влияние магнитогидродинамических волн на функцию распределения электронов. Квазилинейный двумерный в скоростном пространстве оператор моделирует электронное затухание плазменных собственных волн. Динамика процесса описана в условиях изменяющейся со временем фазовой скорости, а, следовательно, и фазового резонанса на основе хорового излучения во время суббури. Это позволило нам объяснить ускорение и нагрев энергетичных электронов, удваивающих свою энергию во время стадии суббури.